SOLATVR - mobile application for children / Muhamad Shazwan Rosli - Rosli, Muhamad Shazwan (2020)
Islam is a religion that has five pillars which a Muslim need to follow. One of the pillars is perform prayer (Salah). Salah is performed five times a day as their obligation as a Muslim. For children that reach seven, parents may urge their children to pray regularly and when their children at ten, their children may be admonished if their children does not perform pray. The problem faced by the children is to remember the movement process in Salah. Current method used in Salah educations which is by book is less attractive for children to learn. Therefore, this project is to propose an innovative way to help children learn about Salah by using virtual reality technology in mobile application. The objectives of this project are to identify the user requirement of SolatVR mobile application, to design and to develop SolatVR mobile application for children. The scope of this project is for seven to ten years old. They will learn about the step by step of process of performing Salah which includes physical movement and recitation. There are five types of Salah which are Subuh, Zohor, Asar, Maghrib and Isyak. This project used Agile Methodology approach to develop SolatVR mobile application. Agile methodology is divided into four phases which are plan, design, develop and test. Based on the deliverables has been discussed. Based on the testing result at the end of the Agile methodology, it shows a positive feedback from the children aged from seven to twelve years old. As conclusion, SolatVR mobile application may help children to remember and easy to understand about the process of performing Salah.